Modelado de componentes académicos utilizando el estándar IMS – LD y marcos de referencia conceptual para la representación de resultados de aprendizaje - Riofrío Granda, Argenis Fabricio (2014)
This research is structured in two parts, the first on modeling educational components using a standard e-learning appropriate for the process and the other is the application of Conceptual Reference Frameworks for representing learning outcomes in order to meet the need for interoperability of content in educational settings. For the first part of this research an IMS LD standard was initially proposed, but in the development of this subject the advantages, disadvantages, and the current state of the standard will address and define its feasibility of application seeking them alternatives to rescue some of the features of standard, as is the case with CC IMS application, and to apply it to the EVA. The second part is geared to define a Conceptual Framework to represent competences and learning outcomes where some of most relevance will be discussed as ISO / IEC TR 24763: 2011, ICOPER, PALO, and related com LOM standard, RCD, RCDEO to finally make its adaptation in the virtual platform.